SUBTYPES OF MASKED HYPERTENSION AND THEIR ASSOCIATIONS WITH TARGET ORGAN DAMAGE IN UNTREATED CHINESE PATIENTS. (June 2018) - Zhang, D.Y.; Cheng, Y.B.; Guo, G.H.; Xu, T.Y.; Yang, Y.; Li, J.J.; Sheng, C.S.; Huang, Q.F.; Wang, J.G.; Li, Y.
Abstract : Objective: Masked hypertension is office normotension in the presence of ambulatory hypertension, which can be subdivided into isolated daytime, isolated nighttime or day-night hypertension. However, no previous studies contrasted the subtypes of masked hypertension in their associations with target organ damage. Design and method: Consecutive untreated patients referred for ambulatory blood pressure (BP) monitoring to our Hypertension Clinic were recruited. The cutoff values for daytime and nighttime hypertension were a BP of 135/85 mmHg and 120/70 mmHg, respectively. Measures of target organ damage, including left ventricular mass index (LVMI), carotid-femoral pulse wave velocity (cfPWV) and urinary albumin-to-creatinine ratio (ACR), were determined. Results: The 1808 participants (mean age, 51 years; women, 52%) included 30.4% normotensive subjects, and 37.2% with masked hypertension, among whom 18% had isolated daytime hypertension, 12% isolated nighttime hypertension, and 70% day-night hypertension. After multivariate adjustment, patients with isolated daytime hypertension (7.9 vs 7.5 m/s, P = 0.003) had higher cfPWV than normotensive subjects. While patients with isolated nocturnal hypertension (0.79 vs 0.58 mg/mmol, P = 0.002) had higher urinary ACR than normotensive subjects. Patients with masked day-night hypertension had consistently higher cfPWV (7.8 vs 7.5 m/s, P < 0.001) and urinary ACR (0.74 vs. 0.58 mg/mmol, P < 0.001) than normotensives. For LVMI, no difference (P > 0.11) between any subtypes of masked hypertension and normotension was observed. Conclusions: Masked hypertension was prevalent in this untreated outpatient cohort. Masked daytime hypertension was associated with arterial stiffness while nighttime hypertension was associated with kidney damage and day-night hypertension with both target organ measures.